Chronic subdural hematoma pressure measurement and its correlation with clinical characteristics and postoperative neurological outcome - Abraham, Tinu Ravi; Mathew, Shaju; Balakrishnan, P. K.; John, Ajax; Pareed, Haris Thottathil; Jose, Tom (International Surgery Journal, 2021)
Background: The pressure of the chronic SDH (subdural haemotoma), the age of the patient, preoperative GCS score and midline shift were considered prognostic dependent factors. The study aimed at the significance of the pressure of chronic SDH in the outcome of patients. Methods: A correlation between subdural hematoma pressure and preoperative and postoperative clinical variables such as hematoma volume, midline shift, age, GCS score and postoperative modified ranking scale score as well as complications were assessed and analyzed. Results: According to the pressure of chronic SDH, 56 patients were grouped into 4 groups. In the pressure group <15 cm/h20 group the mean age was 85 and postoperative ranking score was 3 and the recurrence was 21 % while in high pressure group (>25 cm/h20) the mortality was 14% and no recurrence. Conclusions: The pressure of the chronic SDH has significant prognostic value in chronic SDH surgeries.